2019
DOI: 10.1016/j.annemergmed.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to Persistent or High-Risk Opioid Use After a New Prescription From the Emergency Department: Evidence From Washington Medicaid Beneficiaries

Abstract: Objective To describe the overall risk and factors associated with transitioning to persistent opioid or high-risk use after an initial emergency department (ED) opioid prescription. Methods A retrospective cohort study of Washington Medicaid beneficiaries was performed using linked Medicaid and prescription drug monitoring program files. We identified adults who had no record of opioid prescriptions in the prior 12 months, and who filled a new opioid prescription within one day of an ED discharge in 2014. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 47 publications
(47 reference statements)
3
43
0
Order By: Relevance
“…9 Higher quantities and doses are associated with increased risk of overdose 6,7 and, among opioid-naive patients, with higher risk of progression to long-term use. [10][11][12] In 2016, the Centers for Disease Control and Prevention (CDC) published an influential Guideline for Prescribing Opioids for Chronic Pain 6,7 that recommended (among other measures) starting opioid-naïve patients with acute pain on the lowest effective dose, generally 3-7 days' supply. Multiple policy initiatives have also promoted lower-risk prescribing, ranging from prescription drug monitoring programs (PDMPs) 13 to insurance coverage limitations.…”
Section: Introductionmentioning
confidence: 99%
“…9 Higher quantities and doses are associated with increased risk of overdose 6,7 and, among opioid-naive patients, with higher risk of progression to long-term use. [10][11][12] In 2016, the Centers for Disease Control and Prevention (CDC) published an influential Guideline for Prescribing Opioids for Chronic Pain 6,7 that recommended (among other measures) starting opioid-naïve patients with acute pain on the lowest effective dose, generally 3-7 days' supply. Multiple policy initiatives have also promoted lower-risk prescribing, ranging from prescription drug monitoring programs (PDMPs) 13 to insurance coverage limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Rising trends in ED opioid prescriptions is a public health concern, given studies have demonstrated the potential for these medications to be misused, diverted, or lead to opioid related deaths [ 19 , 20 ]. The data within this study elucidate recent trends in opioid prescriptions in relation to common diagnoses associated with opioid prescriptions, amount and type of opioid prescribed, and provider type (i.e., attending physician, NP/PA, and resident).…”
Section: Discussionmentioning
confidence: 99%
“…13 This strategy may reduce the risk of persistent use, which has been associated with prescriptions for larger volumes of tablets. 7 It also restricts the volume of unused opioids available in the community for misuse by others. In our EDs however, over three-quarters of discharge prescriptions had no reduction in pack size, allowing for a maximum supply of tablets under the PBS to be dispensed.…”
Section: Discussionmentioning
confidence: 99%
“…A recommended safeguard is to limit the number of opioid tablets supplied, to match the expected duration of severe pain 13. This strategy may reduce the risk of persistent use, which has been associated with prescriptions for larger volumes of tablets 7. It also restricts the volume of unused opioids available in the community for misuse by others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation